Current trends in the use of O-(2-[18F]fluoroethyl)-L-tyrosine ([18F]FET) in neurooncology - Stegmayr, Carina; Stoffels, Gabriele; Filß, Christian; Heinzel, Alexander; Lohmann, Philipp; Willuweit, Antje; Ermert, Johannes; Coenen, Heinz H.; Mottaghy, Felix M.; Galldiks, Norbert; Langen, Karl-Josef (Nuclear medicine and biology, 2021)
The diagnostic potential of PET using the amino acid analogue O-(2-[18F]fluoroethyl)-L-tyrosine ([18F]FET) in brain tumor diagnostics has been proven in many studies during the last two decades and is still the subject of multiple studies every year. In addition to standard magnetic resonance imaging (MRI), positron emission tomography (PET) using [18F]FET provides important diagnostic data concerning brain tumor delineation, therapy planning, treatment monitoring, and improved differentiation between treatment-related changes and tumor recurrence. The pharmacokinetics, uptake mechanisms and metabolism have been well described in various preclinical studies. The accumulation of [18F]FET in most benign lesions and healthy brain tissue has been shown to be low, thus providing a high contrast between tumor tissue and benign tissue alterations. Based on logistic advantages of F-18 labelling and convincing clinical results, [18F]FET has widely replaced short lived amino acid tracers such as L-[11C]methyl-methionine ([11C]MET) in many centers across Western Europe. This review summarizes the basic knowledge on [18F]FET and its contribution to the care of patients with brain tumors. In particular, recent studies about specificity, possible pitfalls, and the utility of [18F]FET PET in tumor grading and prognostication regarding the revised WHO classification of brain tumors are addressed.